Three dimensional model of the runup of nonlinear surface gravity waves on the shallow water coastal slope - Abbasov, Iftikhar Balakishievich (Computational Continuum Mechanics, 2013)
The paper is devoted to three-dimensional numerical modeling of a runup of nonlinear surface gravity waves based on Navier–Stokes equations. The three-dimensional formulation of the problem is considered, and the boundary and initial conditions are described. The decomposition method for physical processes is used to construct a discrete model capable of accounting for the factor of filled cells. Features of a design of the simulated three-dimensional shallow water area are described. Three-dimensional models of the staged runup of surface gravity waves on the coastal slope are presented. The wave processes occurring at the runup and back draft of nonlinear surface gravity waves are described.
Keywords: 3D modelling of runup; breaking waves; Navier–Stokes equations; decomposition method; shallow water area; runup and back draft of surface waves